ANALISIS KEMANDIRIAN BELAJAR SISWA DALAM PEMBELAJARAN KONSEP IPAS DI SEKOLAH DASAR - Lutfia Fuziah; Tarpan Suparman; Depi Prihamdani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education plays a vital role in developing independent and high-quality human resources. This study aims to analyze the learning independence of fifth-grade students in Integrated Science, Mathematics, and Social Studies (IPAS) lessons at SDN Kertajaya II. The method used was descriptive qualitative research through observation, interviews, and documentation. The results of this study indicate that students’ learning independence is not yet uniform, as evidenced by the presence of students who lack self-confidence and remain dependent on others. Factors influencing independence include motivation, curiosity, and critical thinking skills. The roles of teachers and parents influence the development of students’ independence in fostering a sense of responsibility in the learning process; therefore, the development of independent learning is crucial for students to improve the quality of their learning outcomes.